Identitas Perempuan Aceh pasca Pemberlakuan Syari‘ah Islam: Sebuah Kajian Kepustakaan - Sri Roviana (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2016)
Women’s identity of Aceh is an important entity within the contemporary political condition of Aceh. Many problems are faced by Acehnese women, when they meet a regime having bias gender in manifesting Islamic sharī‘a which is already formalized within the qanun (formal regulation in Aceh.) Many qanuns have hampered women’s activities and identities. Debates arose questioning whether Islamic sharī‘a should be formally legalized or it is just sosial ethics. This study, for its basic references, bases on literatures already written by researchers who studied sharī‘a and Aceh. After the data found from those literatures, hence they are analyzed by textual and content analysis.